(untitled) (Світ фінансів, 2017)
Пожар А. А. Формування сервісної інфраструктури системи кредитної кооперації України на регіональному рівні. Розкрито особливості розбудови кредитної кооперативної системи України, зокрема – її сервісної інфраструктури. Запропоновано шляхи розвитку окремих елементів сервісної інфраструктури системи кредитних спілок і доведено доцільність їх поетапного створення від регіонального (обласного) рівня до державного. Pozhar A. Forming of Ukrainian credit cooperative system service infrastructure at the regional level. The article is dedicated to peculiarities of development of Ukrainian credit cooperative system, particularly to its service infrastructure. The author proposes the ways of the development of some elements of service infrastructure of the system of credit cooperatives and proves the expediency of its initial creation at the regional level (the level of oblast) and then – at the level of state.